EMPAT PILAR PENDIDIKAN DALAM MENCIPTAKAN MUTU PENDIDIKAN YANG BERBUDAYA - Desi Yuliantari, Ni Wayan (LPM IHDN Denpasar, 2015)
The problems of education in Indonesia is quite compleks and greatly affect learning outcomes and outputs produced a school. problems of education in Indonesia was impressed throwing responsibility. As if the government is guilty, guilty schools and so on. Advancing whereas education is a joint responsibility. Bring our determination together so that educational goals can be achieved through a process of cooperation and good communication between the family, pemeritah, school and community as the four pillars that support the implementation of education in Indonesia to deliver qualified individuals and competitiveness, as well as the four pillars of education has a role which isvery important in improving the quality of education in Indonesia that can make climate or condition of an educational institution that is more secure. Education Quality cultured based curriculum in 2013 through the religious aspects, social aspects, aspects of knowledge and skills aspects, so as to realize the man who is faithful and devoted to God Almighty, noble, healthy, berilmum, capable, creative, independent, and become citizens democratic, and accountable.